Novel Graphene Electrode for Retinal Implants: An in vivo Biocompatibility Study - Nguyen, Diep; Valet, Manon; Dégardin, Julie; Boucherit, Leyna; Illa, Xavi; de la Cruz, Jose; del Corro, Elena; Bousquet, Jessica; Garrido, Jose A.; Hébert, Clément; Picaud, Serge (Frontiers in Neuroscience, 2021)
Evaluating biocompatibility is a core essential step to introducing a new material as a candidate for brain-machine interfaces. Foreign body reactions often result in glial scars that can impede the performance of the interface. Having a high conductivity and large electrochemical window, graphene is a candidate material for electrical stimulation with retinal prosthesis. In this study, non-functional devices consisting of chemical vapor deposition (CVD) graphene embedded onto polyimide/SU-8 substrates were fabricated for a biocompatibility study. The devices were implanted beneath the retina of blind P23H rats. Implants were monitored by optical coherence tomography (OCT) and eye fundus which indicated a high stability in vivo up to 3 months before histology studies were done. Microglial reconstruction through confocal imaging illustrates that the presence of graphene on polyimide reduced the number of microglial cells in the retina compared to polyimide alone, thereby indicating a high biocompatibility. This study highlights an interesting approach to assess material biocompatibility in a tissue model of central nervous system, the retina, which is easily accessed optically and surgically.